2020
DOI: 10.18011/bioeng2020v14n3p274-282
|View full text |Cite
|
Sign up to set email alerts
|

Cultivo Da Rúcula Em Sistema Hidropônico Sob Diferentes Concentrações De Sais

Abstract: Objetivou-se com o presente trabalho avaliar diferentes concentrações de sais na solução nutritiva proposta por Furlani (1999) em cultivo hidropônico de rúcula no sistema deep film techinique (DFT) em ambiente protegido. O delineamento utilizado foi inteiramente casualizado (DIC) com quatro repetições, sendo os tratamentos cinco concentrações de sais: 33%, 67%, 100%, 133% e 167% em relação a concentração original com adaptação do nutriente cobre na concentração 0,064 mg L -1 . As mudas foram conduzidas durante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Despite the favorable response of 125%, it was observed that the plants were 5.2% higher than the 100% rate, with a difference of 9.4% in the number of stems (Figure 1). [11] evaluating the concentrations of the same solution in the present study in arugula cultivation, observed better productive performance in nutrient concentrations between 67 and 100%. The authors emphasize that rates higher than 100% increase the production cost, without generating significant increases in the accumulation of nutrients, such as nitrogen, phosphorus, and potassium in arugula leaves.…”
Section: Resultssupporting
confidence: 61%
“…Despite the favorable response of 125%, it was observed that the plants were 5.2% higher than the 100% rate, with a difference of 9.4% in the number of stems (Figure 1). [11] evaluating the concentrations of the same solution in the present study in arugula cultivation, observed better productive performance in nutrient concentrations between 67 and 100%. The authors emphasize that rates higher than 100% increase the production cost, without generating significant increases in the accumulation of nutrients, such as nitrogen, phosphorus, and potassium in arugula leaves.…”
Section: Resultssupporting
confidence: 61%